Simple Teaching Tools: Efforts to Improve Mastery of Direct Current Electrical Materials by Utilization in Physics - Limba, Anatasija; Huwae, Imanuel V.; Tamaela, Elsa (KnE Social Sciences, 2024)
A teaching tool is a collection of concrete objects that are purposefully developed or created to make the learning process more relevant and effective. Our findings at one of Ambon City’s high schools revealed that there were no teaching tools for direct current (DC) power. Hence, learning has only been accomplished via the lecture technique. This impacted students’ poor mastery of the material. This study aimed to improve mastery of the DC electricity topic using basic teaching methods in physics education. This type of study consists of a one-group pre and post-test. Data were examined with N-Gain to measure the increase in mastery of the subject after students completed the learning procedure. The research sample consisted of 22 students from Class XII-3. According to the study’s findings, 45.5% of students with high qualifications and 54.5% of students with medium qualifications improved their mastery of the material under study. Thus, it is possible to conclude that the use of simple teaching tools in DC electricity material in physics education can improve students’ comprehension of the topic at hand. Keywords: simple teaching tools, material mastery, direct current electricity